2017
DOI: 10.1371/journal.pone.0169322
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness and Falls in Obese Inpatients Undergoing Metabolic Rehabilitation

Abstract: AimThe relationship between dizziness and falls in the obese population is a relatively unexplored issue. The aims of the present study were to define the 1-year prevalence of dizziness in an obese inpatient population undergoing metabolic rehabilitation and to investigate possible correlations with fall events.Materials and MethodsWe recruited 329 obese subjects: 203 female (BMI 43,74 kg/m2 ± 0.5 SE; age 17–83 years, 58.33 ± 0.9 SE) and 126 male (BMI 44,27kg/m2 ± 0.7 DE age 27–79 years, 58.84 ± 1 SE). To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…This feature of the only dizziness group remained in the adjusted multivariate regression analysis ( Table 5 ). Moreover, the imbalance group showed relatively higher odds in the obesity three group, similar to the previous studies on postural instability in the obese group ( 28 ). Obesity is a known risk factor for postural instability and imbalance.…”
Section: Discussionsupporting
confidence: 89%
“…This feature of the only dizziness group remained in the adjusted multivariate regression analysis ( Table 5 ). Moreover, the imbalance group showed relatively higher odds in the obesity three group, similar to the previous studies on postural instability in the obese group ( 28 ). Obesity is a known risk factor for postural instability and imbalance.…”
Section: Discussionsupporting
confidence: 89%
“…the body image) on body schema in obesity; it can simultaneously establish the efficacy of a rehabilitative approach based on multiple sensory inputs and their integration. Obesity is a growing global health issue, but since its complexity links medical, neuropsychological and psychopathologic dimensions, all these components have to be considered in the light of the possible outcome on more efficient interventions in rehabilitation and fall prevention [69].…”
Section: Discussionmentioning
confidence: 99%
“…Age should be considered when applying the results of the current study in general practice. With regard to obese participants, prior studies have shown an association between postural symptoms and obesity . However, an interaction of BMI on the relationship between sodium and potassium with BP has not yet been reported .…”
Section: Discussionmentioning
confidence: 94%